Kesenjangan Implementasi Penelitian Kemasyarakatan dalam Proses Restorative Justice bagi Pelaku Dewasa dalam Tindak Pidana Ringan - Trio Sandra Wijaya; Muhamad Adystia Sunggara (Badan Strategi Kebijakan Hukum, 2025)
This study examines the gap between regulation and practice in the use of the Community Research Report (Litmas) in applying restorative justice for adult offenders. Normatively, Litmas has been legitimized by Law No. 22 of 2022 on Corrections and Supreme Court Circular No. 1 of 2021, yet its practical use remains limited. The research aims to explain the determinants of Litmas effectiveness while emphasizing its importance within the criminal justice system. Using a normative juridical method and descriptive qualitative analysis, and combining Soerjono Soekanto’s theory of legal effectiveness, George Edwards III’s policy implementation theory, and gap analysis, this study finds that the limited use of Litmas is caused by the absence of detailed technical guidelines, weak institutional capacity and professionalism of probation officers, poor inter-agency coordination, the dominance of a retributive legal paradigm in legal culture, insufficient political support, and the lack of information technology utilization. The conclusion highlights that the regulatory and practical gap is systemic and multidimensional, and the effectiveness of Litmas can only be achieved by strengthening six interrelated determining factors. This study underscores the importance of Litmas not only normatively as a regulatory mandate but also practically as a strategic instrument to deliver more humane justice, reduce prison overcrowding, and reinforce the legitimacy of restorative justice in Indonesia.